Implementasi Algoritma Text Mining dan Cosine Similarity untuk Desain Sistem Aspirasi Publik Berbasis Mobile (Komputika : Jurnal Sistem Komputer, 2022)
The existence of DPRD in the regions is often referred to as a representative function because it is tasked with voicing the people's aspirations and acting on behalf of the people (representative government) in the legislative field. So far, most people still have difficulty conveying their aspirations to the Regional People's Representative Council (DPRD) of Makassar City and getting input on the aspirations submitted by the community to the Regional People's Representative Council (DPRD). The research problem is how to process data on people's aspirations to be categorized based on mobile-based commissions and data on people's aspirations to get input from the Regional People's Representative Council (DPRD) on the aspirations they send. The purpose of this research is to build an application that can accommodate people's aspirations and then classify them and forward those to the appropriate mobile-based commission to provide a system that DPRD can use to provide input. The research method used is the Text Mining and Cosine Similarity algorithm. The result of the research is that the application uses a combination of text mining methods and Cosine similarity to measure the functional similarity of each commission with the aspirations inputted by the community so that aspirations can be right on target. The conditions for determining the multi-commission must be 75% of the maximum value.